The importance of school snacks for primary school-aged children nutritional support as the foundation of Sekolah Generasi Maju in Indonesia - Saptawati Bardosono; Pittara Pansawira (World Nutrition Journal, 2021)
As a developing country, Indonesia is still burdened with high prevalence of child malnutrition including those in primary school. One of the main factors affecting nutritional status of children is snack consumption in school. School snacks are expected to be able to contribute to nutritional requirements. This narrative review is written to collect information and knowledge regarding nutritional status, nutritional requirements, factors determining nutritional status of primary school children and, lastly, recommended school snacks. This review also acts as a basic information for school snacks program establishment.